Animal and vegetable protein intake and malnutrition in older adults: a multicohort study - Adrián Carballo-Casla; Mercedes Sotos-Prieto; Esther García-Esquinas; Ellen A Struijk; Francisco Félix Caballero; Amaia Calderón-Larrañaga; Esther Lopez-Garcia; Fernando Rodríguez-Artalejo; Rosario Ortolá (Elsevier, 2024)
Objectives: Malnutrition is a global concern in older adults, as it negatively affects morbidity and mortality. While higher animal protein intake may help prevent and treat malnutrition, it might also increase the risk of chronic diseases and death. Conversely, vegetable protein intake might have a lower anabolic effect and not be as effective to improve nutritional status. We studied whether animal and vegetable protein intake are associated with changes in nutritional status in older adults. Design: We used pooled data from two Spanish cohorts: the Seniors-ENRICA 1 and Seniors-ENRICA 2. Settings and participants: 2,965 community-dwelling adults aged 62-92 years. Measurements: Protein intake was estimated at baseline via an electronic, validated diet history. Nutritional status was assessed at baseline and after 2.6 years with the GLIM (Global Leadership Initiative on Malnutrition) phenotypic criteria: weight loss, low body mass index, and reduced muscle mass. The odds of improvements in nutritional status were assessed with logistic regression models, extensively adjusted for potential confounders. Results: Higher animal and vegetable protein intake were associated with improvements in nutritional status [odds ratios (95% confidence intervals) per 0.25 g/kg/day were 1.15 (1.00, 1.32) and 1.77 (1.35, 2.32), respectively]. Cereal protein intake drove most of the latter association [2.07 (1.44, 2.98)]. Replacing 0.25 g/kg/day of total animal protein, meat, or fish protein (but not dairy or egg protein) with vegetable protein was associated with improvements in nutritional status [1.54 (1.13, 2.09), 1.70 (1.20, 2.41), and 1.77 (1.18, 2.64), respectively]. Conclusions: Higher animal and, especially, vegetable protein intake were associated with improvements in nutritional status in older adults. Replacing total animal protein, meat, or fish protein with vegetable protein may help improve malnutrition.